Postoperative C-Reactive Protein/Albumin Ratio: A New Era in Predicting Mortality After Coronary Artery Bypass Grafting - Toprak, Burak; Bora, Rıdvan (Scientific Reports in Medicine, 2025)
Aim: Coronary artery bypass grafting is one of the most commonly performed surgical procedures for patients with advanced coronary artery disease. However, postoperative complications and mortality remain significant concerns. Systemic inflammation and nutritional status are crucial factors influencing surgical outcomes. The prognostic value of biomarkers that simultaneously assess these parameters in the postoperative period remains unclear. The C-reactive protein to albumin ratio has emerged as a novel biomarker reflecting both inflammation and nutritional status. This study aims to evaluate the role of postoperative C-reactive protein to albumin ratio in predicting early mortality in patients undergoing coronary artery bypass grafting. Specifically, the impact of postoperative inflammatory response and nutritional status on patient outcomes will be analyzed. Methods: This retrospective observational study included 350 patients who underwent coronary artery bypass grafting. Preoperative and postoperative biochemical markers, including C-reactive protein, albumin, and C-reactive protein to albumin ratio, were analyzed. The primary outcome was 30-day mortality. Logistic regression models were applied to assess the independent association between postoperative C-reactive protein to albumin ratio and mortality, adjusting for potential confounders. Results: Patients with higher postoperative C-reactive protein to albumin ratio had significantly increased mortality rates (p = 0.0155). While preoperative values did not show a significant association with mortality (p = 0.5178), postoperative levels emerged as a strong predictor. Elevated postoperative urea levels were also independently associated with mortality (p < 0.0001). Conclusions: Postoperative C-reactive protein to albumin ratio is an independent predictor of early mortality in patients undergoing coronary artery bypass grafting.